miR-936 Suppresses Cell Proliferation, Invasion, and Drug Resistance of Laryngeal Squamous Cell Carcinoma and Targets GPR78 - Lin, Xi-Jun; Liu, Hui; Li, Pei; Wang, Hai-Feng; Yang, An-Kui; Di, Jin-Ming; Jiang, Qi-Wei; Yang, Yang; Huang, Jia-Rong; Yuan, Meng-Ling; Xing, Zi-Hao; Wei, Meng-Ning; et al. (Frontiers in Oncology, 2020)
MicroRNAs (miRs) play important roles in tumor progression. miR-936 has been reported to suppress cell invasion and proliferation of glioma and non-small cell lung cancer. Nevertheless, the function of miR-936 in laryngeal squamous cell carcinoma (LSCC) remains undiscovered. Hence, our study was to investigate the role of miR-936 in LSCC. In our present research, we have testified that miR-936 was substantially downregulated in LSCC tissues compared with adjacent normal tissues. Furthermore, miR-936 could inhibit proliferation, migration and invasion, and improve the sensitivity to doxorubicin and cisplatin of LSCC cells. Additionally, luciferase reporter assays were performed to confirm that GPR78 was a novel target of miR-936, and the protein expression of GPR78 was obviously inhibited by miR-936 in LSCC cells. In summary, our study indicates that the miR-936/GPR78 axis could be both a diagnostic marker and a therapeutic target for LSCC.